2006
DOI: 10.1128/aem.72.5.3716-3723.2006
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Production of Neoculin, a Sweet-Tasting Heterodimeric Protein with Taste-Modifying Activity, by Aspergillus oryzae

Abstract: Neoculin (NCL), a protein with sweetness approximately 500-fold that of sugar, can be utilized as a nonglycemic sweetener. It also has taste-modifying activity to convert sourness to sweetness. NCL is a heterodimer composed of an N-glycosylated acidic subunit (NAS) and a basic subunit (NBS), which are conjugated by disulfide bonds. For the production of recombinant NCL (rNCL) by Aspergillus oryzae, ␣-amylase with a KEX2 cleavage site, -K-R-, was fused upstream of each of NAS and NBS and the resulting fusion pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…In general, the production levels of proteins from higher eukaryotes (animals and plants) by A. oryzae are much lower than those of homologous (fungal) proteins (15,16,31,41). It has been shown that the bottleneck in the production of heterologous proteins is not caused by low expression of the heterologous gene but is due to posttranscriptional processes in the secretory pathway (42).…”
mentioning
confidence: 99%
“…In general, the production levels of proteins from higher eukaryotes (animals and plants) by A. oryzae are much lower than those of homologous (fungal) proteins (15,16,31,41). It has been shown that the bottleneck in the production of heterologous proteins is not caused by low expression of the heterologous gene but is due to posttranscriptional processes in the secretory pathway (42).…”
mentioning
confidence: 99%
“…When the UPR is triggered, the expression of a set of UPR-associated proteins, including molecular chaperones, vesicular traffic components, and ERassociated degradation (ERAD) proteins, is upregulated in an attempt to resolve the ER stress by increasing the folding, transport, and degradation of proteins (13). Constitutive upregulation of UPR by the expression of the activated form of the transcription factor HacA was shown to improve the production of bovine chymosin in Aspergillus niger (14) and the plant taste-modifying protein neoculin in A. oryzae (7). Although these observations suggest that ER stress is a major hindrance for heterologous protein production in filamentous fungi, the underlying cause of the ER stress associated with heterologous protein expression remains unclear.…”
mentioning
confidence: 99%
“…More recently, the ability of the species to secrete large amounts of proteins has extended its industrial use to include heterologous protein production (28,46,63,64). A. oryzae has no known sexual cycle and has traditionally been classified within the Fungi Imperfecti (the Deuteromycota), or "mitosporic" fungi (35).…”
mentioning
confidence: 99%